Immunosorbent Electron Microscopy For Detection Of Viruses - Katz, David (Adv Virus Res, 1984)
This chapter discusses the newer modifications of immunosorbent electron microscopy (ISEM) methods in both plant and animal virology. ISEM methods presented in the chapter include all the techniques where the “solid phase principle” is essential in a way similar to other solid phase immunoassays. These methods include (1) the antibody-coated grid technique (AB-CGT); (2) the protein A-coated grid technique (PA-CGT); (3) the protein A-coated bacteria technique (PA-CBT); and (4) the antigen-coated grid technique (AG-CGT). In all ISEM methods, one of the components of the system is adsorbed to a solid phase. In AG-CGT, PA-CGT, and AB-CGT, one of the reagents is adsorbed to an electron microscopic grid, while in PA-CBT protein A is naturally present on the surface of a bacterium that serves as a solid support. In ISEM methods, the viruses can be statistically evaluated and numerically expressed as number of virions per unit of area, and can, therefore, be statistically evaluated. Thus, these methods optimize the results of a test by quantifying the effects of the quality of the supporting grid, the time of adsorption, the pH, the presence of salts, and the type of staining. The ISEM also permits a detailed study of antigenic variations in the same genus of virus, and thus would visually pinpoint the type or strain differences.